Adherence of Packing Defects in Soluble Proteins - Fernandez, Ariel (2003)
For protein structure to prevail in water, its backbone hydrogen bonds must be shielded from water attack, requiring a cluster of “wrapping” nonpolar groups. Thus, underwrapped regions are adhesive, as exogenous removal of surrounding water becomes thermodynamically favorable. Here we measure the average adhesive force exerted by an underwrapped hydrogen bond on a test hydrophobe and thus define a new interactivity constant.